On the numerical solution of a mathematical model for the concrete carbonation with a non-uniform diffusivity coefficient - Zambrano Fernandez, Marcos (2021)
In this research, a mathematical model to determine the concentration of concrete carbonation is investigated using several numerical schemes which provide the distribution of carbonation in a concrete region. This model considers an Arrhenius-type relation which implies a non-uniform diffusion coefficient for a reaction- diffusion problem in the model. To perform the computations of the model investigated, the finitedifferences and finite-volume methods are employed which are implemented in the mathematical software GNU-Octave and the finite-volume software OpenFOAM respectively.